Modulation of Immunoregulatory Properties of Mesenchymal Stromal Cells by Toll-Like Receptors: Potential Applications on GVHD - Bruno Sangiorgi; Rodrigo Alexandre Panepucci (Stem Cells International)
In the last decade, the immunomodulatory properties of mesenchymal stromal cells (MSCs) have attracted a lot of attention, due to their potential applicability in the treatment of graft-versus-host disease (GVHD), a condition frequently associated with opportunistic infections. The present review addresses how Pathogen-Associated Molecular Patterns (PAMPS) modulate the immunosuppressive phenotype of human MSCs by signaling through Toll-like receptors (TLRs). Overall, we observed that regardless of the source tissue, human MSCs express TLR2, TLR3, TLR4, and TLR9. Stimulation of distinct TLRs on MSCs elicits distinct inflammatory signaling pathways, differentially influencing the expression of inflammatory factors and the ability of MSCs to suppress the proliferation of immune system cells. The capacity to enhance the immunosuppressive phenotype of MSCs through TLRs stimulation might be properly elucidated in order to improve the MSC-based immunotherapy against GVHD.